Implementasi Ekstrakurikuler Baca Tulis Al-Qur’an dalam Upaya Meningkatkan Kemampuan Baca Tulis Al-Qur’an di MTsN 2 Medan - Neliwati Neliwati; Annisa Oktavera; Nur Adilah Rangkuti; Nur Fauziyah (FKIP, Universitas Palangka Raya, 2025)
This research is useful to understand how the extracurricular Quran reading and writing program is implemented at MTS N 2 Medan with the aim to improve students' Quran literacy. The researchers used qualitative methodology as their approach. The focus of the qualitative approach is on in-depth observation. Thus, it is possible to build a more comparative analysis through research using qualitative research methods. The implementation of extracurricular activities of reading and writing the Qur'an includes planning, methods and steps of learning activities, and how learning should be measured, according to the results that can be achieved by researchers. The right approach should be used as a motivator to achieve the desired results in an effort to improve the ability to read and write the Qur'an. Pupils should strive to be more imaginative, creative and engaged. The right approach is needed in such endeavors to ensure that students understand and learn well.